Permodelan Sistem Pembayaran SPP Berbasis Sms Gateway Pada SMK Negeri 1 Bandar Lampung - Adhie Thyo Priandika; Afitra Tanthowi; Donaya Pasha (Journal of Engineering and Information Technology for Community Service, 2022)
SMK Negeri 1 Bandar Lampung is an educational institution located on Jl. Morotai Island Jl. Morotai Island No. 33, Jagabaya III, Sukarame, Bandar Lampung City, Lampung 35122, Indonesia. SMK Negeri 1 Bandar Lampung has expertise programs, namely Dressing, Catering, Information and Communication Technology, Animation and Business and Management. As for the SPP payment system at SMK Negeri 1 Bandar Lampung it is still done manually, where the Administrative Officer still uses a book to record SPP payment data. This causes SPP data storage is still in the form of archives, where data storage media like this are easy to damage or lose, and archives that accumulate make the performance of school staff not good. From this problem, the idea emerged to create a desktop-based application and an sms gateway, in which it can manage payment transaction data and provide information to parents related to tuition transactions. The methodology used in making this application is the Waterfall method. The programming language used is Java Neatbeans, the database uses MySQL and Gammu as a tool to connect the SMS Gateway. Supported by the existence of a computer at the institution. With the application of the desktop-based tuition payment information system and SMS Gateway, it is hoped that it will make it easier to manage transactions and provide information to parents